Hard spheres at a planar hard wall: Simulations and density functional theory - Davidchack, R.L.; Laird, B.B.; Roth, R. (Condensed Matter Physics, 2016)
Hard spheres are a central and important model reference system for both homogeneous and inhomogeneous fluid systems. In this paper we present new high-precision molecular-dynamics computer simulations for a hard sphere fluid at a planar hard wall. For this system we present benchmark data for the density profile ρ(z) at various bulk densities, the wall surface free energy γ, the excess adsorption Γ, and the excess volume vex, which is closely related to Γ. We compare all benchmark quantities with predictions from state-of-the-art classical density functional theory calculations within the framework of fundamental measure theory. While we find overall good agreement between computer simulations and theory, significant deviations appear at sufficiently high bulk densities. Твердi сфери є центральною i важливою моделлю системи вiдлiку для однорiдних i неоднорiдних плинних систем. У цiй статтi ми представляємо новi високоточнi моделювання методом молекулярної динамiки для плину твердих сфер бiля плоскої твердої стiнки. Для цiєї системи ми представляємо данi по
профiлю густини ρ(z) для рiзних об’ємних густин, поверхневої вiльної енергiї γ, надлишкової адсорбцiї
Γ i надлишкового об’єму vex, який тiсно пов’язаний з Γ. Ми порiвнюємо всi величини з передбаченнями з оригiнальних розрахункiв теорiї класичного функцiоналу густини в рамках теорiї фундаментальної
мiри. Хоча ми отримуємо вцiлому добре узгодження мiж комп’ютерним моделюванням i теорiєю, значнi
вiдхилення появляються при достатньо високих об’ємних густинах.